Collective Bargaining Perspectives - Craig, A.; Waisglass, H. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1968)
After an examination of the socio-economic environment within which collective bargaining functions, the authors study the parties involved, the structures of negotiating units, the procedures for resolving conflicting interest disputes. They also present some of the major outputs of the collective bargaining system and formulate a few suggestions about the future functionning of collective bargaining and the role and structures of union and other groups within the system.